Vestibular Disorders: Pearls and Pitfalls - Choi, Woo Young; Gold, Daniel R. (Seminars in Neurology, 2019)
Dizziness and vertigo are symptoms that commonly lead patients to seek neurologic or emergency care. Because symptoms are often vague and imprecise, a systematic approach is essential. By categorizing vestibular disorders based on the timing, triggers, and duration of symptoms, as well as emphasizing focused ocular motor and vestibular examinations, the majority of vestibular diagnoses can be made at the bedside. This paper will discuss the pearls and pitfalls in the history and examination of the most common acute, episodic, and chronic vestibular disorders.
Keywords: vertigo; dizziness; acute vestibular syndrome; vestibular; HINTS exam